2016
DOI: 10.1080/17518253.2016.1234005
|View full text |Cite
|
Sign up to set email alerts
|

Pure green chemical approach for synthesis of Ag2O nanoparticles

Abstract: In this study, a green chemistry method is reported for the synthesis of Ag 2 O nanoparticles with the utilization of starch molecules as a stabilizing agent. In particular, by simply adjusting the concentration of starch in the reaction media, the structure of A 2 O nanoparticles can be engineered in disc and faceted shapes, which has been analyzed by transmission electron microscopy, UV-Vis spectroscopy, and X-ray diffraction technique. In addition, antibacterial activity of the prepared Ag 2 O nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…From the TEM images (Figure 6c-e) the lattice fringes allow the identification of crystallographic spacing. The d-spacing value of 0.35 nm corresponds to the anatase (101) plane [57,58], whereas the d values of 0.28 nm and 0.16 nm, respectively, represent the plane of (111) and (220) for Ag 2 O species [59][60][61]. These results strongly support the results from powder X-ray diffraction (see above).…”
Section: Electron Microscopy and Energy-dispersive X-ray Spectroscopysupporting
confidence: 85%
“…From the TEM images (Figure 6c-e) the lattice fringes allow the identification of crystallographic spacing. The d-spacing value of 0.35 nm corresponds to the anatase (101) plane [57,58], whereas the d values of 0.28 nm and 0.16 nm, respectively, represent the plane of (111) and (220) for Ag 2 O species [59][60][61]. These results strongly support the results from powder X-ray diffraction (see above).…”
Section: Electron Microscopy and Energy-dispersive X-ray Spectroscopysupporting
confidence: 85%
“…The increased absorption of the samples at pH = 8.5 compared with the rest is due to the rod morphology of NPs, as shown in the FESEM images (Figure 2). Rokade et al [42] have reported that the change of absorption bands is related to morphology of particles, such as Ag 2 O nanopowders.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Absorption peak of metal NPs is conquered by the SPR of leaf extract reduced silver ions (Ag + ) to the Ag 2 O-NPs (Rokade et al 2016).…”
Section: Uv-vis Spectroscopic Studymentioning
confidence: 99%
“…The observed XRD data were matched to the XRD standard data JCPDS le No. 41-1104 and assigned to the planes of the cubic Ag 2 O phase(Rokade et al 2016). The diffractogram showed that synthesized NPs were crystalline cubic structure and the slight modi cation in intensity could be due to binding of leaf extract biomolecules to the surface of NPs(Muthukumar et al 2020a).…”
mentioning
confidence: 99%